The Role of Mastery Goal on Life Satisfaction Using PERMA as A Mediator for College Students - Riyan Hidayat; Sibo Liu; Mohd Rashid Mohd Saad; . Hermandra (Emerging Science Journal, 2023)
This study examined the relationship between mastery goals, including task-based and self-based competence, and positive emotions, engagement, relationship, meaning, and accomplishment (PERMA), which may affect life satisfaction. Mastery goals, PERMA, and life satisfaction were examined using a relationship study model. The current study involved 260 English education programs, with 81 (31.2%) male students and 179 (68.8%) female students. AMOS 18 was used to conduct a confirmatory factor analysis (CFA). The results of the current study demonstrate that task-based competence influences life satisfaction. In contrast, self-based competence was found not to affect life satisfaction. Analysis of SEM revealed significant influences of task-based competence on PERMA and no significant relationships between self-based competence and PERMA. PERMA partially mediates the influence of task-related competence on life satisfaction. The indirect effects of self-based competence on life satisfaction were observed through PERMA as a complete mediator. The novelty of the current research lies in its focus on mastery goals, the target population of college students, and the mediating role of PERMA. These contributions are critical, as teachers or instructors are responsible for developing student well-being and life satisfaction. Doi: 10.28991/ESJ-2023-SIED2-018 Full Text: PDF